Multi-disciplinary rehabilitation for management of diabetes mellitus related neurological and musculoskeletal complications - Sami Ullah; Dilshad Hunain Al Arabia; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2022)
Diabetes Mellitus (DM) is one of the most common metabolic disorders in the world. It can result in several neurological and musculoskeletal (MSK) conditions. These conditions adversely affect the mobility, community functioning and quality of life for the patient with DM. Rehabilitation Medicine Physicians (Physiatrists) can offer both diagnostic and therapeutic interventions for the accurate diagnosis and optimal management of neurological and MSK conditions associated with DM. These include diagnostic tests such as Nerve Conduction Studies and Electromyography, therapeutic interventions in form of pharmacological management of symptoms, prescription of appropriate physical therapy, occupational therapeutic exercise, injections, as well as psychosocial and cognitive interventions. A physiatrist can provide expert advice on musculoskeletal disorders in patients with DM, as they are formally trained in the evaluation, diagnosis, and management of MSK conditions. A multidisciplinary team for DM should include a physiatrist as one of the key members. This can help effectively address neurological and MSK disorders related to DM. Keywords: Rehabilitation Medicine, Physiatry, Physiotherapy, Occupational therapy, Pain management, Assessment, Diabetes Mellitus, Quality of Life.